Are our cities falling behind? A German perspective on the supply for year-round green exercise - Reuß, Konrad; Huth, Christopher (Frontiers in Sports and Active Living, 2025)
Green exercise, defined as physical activity practiced in natural environments, has been recognized for its numerous health benefits, such as improvement of physiological and psychological well-being or social benefits. However, there is a decrease in green exercise, especially during winter. Adverse weather conditions, such as precipitation and cold weather, lead to this decrease. However, another factor might be found in the availability of adequate sports spaces and facilities for green exercise during those conditions. So far, the availability of suitable sports spaces and facilities for urban year-round green exercise, particularly under varying meteorological conditions, remains underexplored. This study aims to assess the supply and suitability of urban sports spaces and facilities for year-round green exercise in Germany on an individual and organizational level. A comprehensive online survey was conducted to assess the supply from an individual-level perspective as well as from an organizational-level viewpoint. Results indicate that the availability of sports spaces and facilities for urban year-round green exercise is rated as adequate on an individual level. However, there are significant variations depending on age, sports type, and individual connection to nature. On the organizational level, however, the suitability of existing sports spaces and facilities is rated low. The study found a strong correlation between perceived accessibility and the likelihood of engaging in green exercise, suggesting that better-designed and promoted facilities could enhance participation rates. Moreover, the lack of adequate courses and information about existing year-round green exercises poses additional barriers that must be addressed by urban planning and sports governance.